Development and validation of a dynamic light scattering-based method for viral quantification: A straightforward protocol for a demanding task - Rene A. Navarro-Lopez; Erika Silva-Campa; Gerardo Santos-López; Adriana Garibay-Escobar (PLoS ONE, 2025)
This study aimed to develop a reliable, rapid method for viral particle quantification using Dynamic Light Scattering (DLS) as an alternative to traditional virological techniques. Conventional methods, such as plaque assays, though widely recognized, are time-intensive and depend on the observation of cytopathic effects, which can be subjective. In this study, Influenza A virus (IAV) supernatants were quantified using DLS and subsequently compared with titers determined by plaque assays and TCID50. DLS measures the fluctuations in light scattering caused by particles in Brownian motion, allowing direct, non-destructive measurement of viral concentration within minutes. Results indicated a strong correlation between the DLS-derived viral titers and those obtained from plaque assays (R2 = 0.9967) and TCID50 (R2 = 0.9984), demonstrating DLS potential as a complementary or alternative method for rapid quantification. The technique non-reliance on cell viability and ability to measure intact viral particles enhance its applicability for assays where infectivity is not the primary concern. Additionally, DLS facilitated the detection of complete viral particles, which is advantageous for vaccine development and antiviral testing. The protocol’s reproducibility across various dilutions, coupled with minimal sample preparation requirements, underscores DLS as a feasible quantification method adaptable for different viral strains. Limitations, including the inability to distinguish between infectious and non-infectious particles, suggest that while DLS serves as a valuable initial quantification tool, further infectivity assessments may be required for comprehensive viral characterization.